HEALTH COUNSELING TO INCREASING KNOWLEDGE AND COMPLIANCE IN HYPERTENSION PATIENTS - Zaenal Fanani; Yunita Rusidah; Shinta Dwi Kurnia; Lailatul Farikhah; Munandiyah Munandiyah (Universitas Muhammadiyah Kudus, 2025)
Hypertension is a silent killer because it often occurs without complaints, symptoms can vary among individuals, and are almost the same as the symptoms of other diseases and can cause several complications including coronary heart disease, stroke and kidney failure. To support appropriate hypertension therapy, health counseling is needed given that knowledge and adherence to the expected therapeutic effect can be achieved. The purpose of this study was to determine the influence of health counseling on increasing patient knowledge and compliance. Primary data collection was carried out from February to March 2023, using the one-group pre and post-test experimental quasi-methods, for 55 respondents. The research instrument used two questionnaires, namely patient knowledge and compliance. Blood pressure was 140/90 in 34 (61,82%) patients and the duration of hypertension was 5 years in as many as 43 (78,2%) patients. The percentage of patients who completed the post-test patient knowledge was as high as 100%, and the percentage of patients who completed the post-test compliance was as high as 63,64%. A significant difference was found between the two data sets (p= 0.000). Patient knowledge and compliance increased significantly from before health counseling to after health counseling.